IEEE 802.11ac sebagai Standar Pertama untuk Gigabit Wireless LAN - Afdhal Afdhal; Elizar Elizar (Universitas Syiah Kuala, 2014)
WLAN is a technology that currently has been used widely. This technology is considered as a data transferring media technology within the LAN/MAN. To ensure that WLAN technology can be used widely in the whole world, the IEEE has set a standard known as 802.11 to be an international standard for the WLAN technology. This standard was appeared in 1997, and has been revised and improved for several times. This improvement is done to anticipate the rapidly grown WLAN market as well as to keep this technology remains effective, efficient, and reliable at any time. At the beginning of 2014, the IEEE has set 802.11ac-2013 as a new standard for WLANs that operate below 6 GHz to achieve a data rate for up to 7 Gbps. The purpose of this article is to describe comprehensively the IEEE 802.11ac standard as a result of recent changes to the regulatory for WLAN technology which is known as the first standard issued by the IEEE for the gigabit WLANs. This article discusses the goals and objectives to be achieved by 802.11ac standard as well as the parts that have been enhanced significantly both in its PHY and MAC layers. This article will also contrast the differences between the 802.11ac standard and previous WLAN standards. Finally it will also explain the level of compatibility and interoperability of 802.11ac standards with some of previous WLAN standard.Keywords: IEEE, 802.11, 802.11ac, Gigabit WLAN